THE EFFECT OF KNOWLEDGE AND REGULATION TOWARD THE ISLAMIC FINANCIAL INDUSTRY DEVELOPMENT - Mansyur Asri; Ernawati Ernawati; Ambo Wonua Nusantara (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
The development of Islamic finance industry in many countries, it has not been in line with the Moslem population, because beside the potential demand reason, theIslamic financial industry services is also influenced by knowledge and regulation support.This study aims to determine the effect of knowledge and regulation toward the development of the Islamic financial industry. The study uses secondary data from ICD publications in  2013-2019 period for 41 countries. The data were analyzed using the panel data regression and moderating variables, where knowledge has been estimated as a moderating variable for the regulations effect on the Islamic financial industry development. The results showed that: (1) the regulation and the level of knowledge had a positive significant effect to the  Islamic finance industry development; and (2) the knowledge variable becomes  the moderator between regulation and the development of the Islamic financial industry. This shows that the knowledge would encourage the strengthening of the regulatory effect on the development of Islamic finance.